The Resolution Of The Cornucopian-Ecologist Issue On Global Warming-Climate Change - Lane, Jan Erik (Archives of Business Research, 2014)
Cornucopians and ecologists have debated the hypotheses of global warming as a result of the emission of greenhouse gases for several decades, focusing upon different interpretations of risk: resilience against precaution. One can now employ recently available data on GDP, energy consumption, emissions and global average temperature to decide between these two positions. The cornucopian position is wrong, the evidence strongly indicates. Key words: greenhouse gases, global temperature, energy consumption, GDP per capita, cornucopians, ecologists, Simon, Wildavsky, Lomborg, Lovelock, CPRs, logic of collective action.